(untitled) (KYAMC Journal, 2022)
Covid-19 had been identified as an acute respiratory disease and many other systemic illnesses, causing unusual morbidity and death, particularly in older people and other people with co-morbidities. The disease is caused by an extremely infectious, super rapidly spreading and super-promptly mutating novel coronavirus, now known as the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2 virus). Covid-19 became a pandemic in 2020 and 2021. Though its pandemic nature is now declining, it is still in existence in many parts of the world, causing substantial mortality and morbidity. The Wuhan Municipal Health Commission of Hubei province, officially notified it first on December 31, 2019, though the first date of symptom onset of a cavid-19 case was first recorded on December 8, 2019 on basis of the patient’s recall during the investigation in the Wuhan city of central China. China publicly had circulated the genetic make-up of the causative virus on January 12, 2020. From the 1st January, 2020 onwards, the WHO (World Health Organization) had worked on it several times at several levels till March 11, 2020, When WHO deeply notified its alarming spread and severity, characterizing it as a pandemic. It had created a severe panic all over the world, interfering with life, health, economy, trade, commerce, livelihood and living standard of people. This Covid-19 had taught us a myriad of lessons how to tackle and handle catastrophic massive disasters in emergent situations, probing into our limitations and requirements and emphasizing on local, regional. national and international awareness, cooperation and coordination. KYAMC Journal Vol. 13, No. 03, October 2022: 170-176